New midpoint and trapezoidal-type inequalities for prequasiinvex functions via generalized fractional integrals - KERMAUSUOR, Seth; NWAEZE, Eze R. (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
In this work, we establish some new midpoint and trapezoidal type inequalities for prequasiinvex functions via the Katugampola fractional integrals. Some of the results obtained in this paper are generalizations of some earlier results in the literature. Mathematics Subject Classification (2010): 26A33, 26A51, 26D10, 26D15. Received 12 January 2020; Accepted 14 June 2021.